(untitled) (Research, Society and Development, 2022)
The financing of the Unified Health System (SUS) is an advance in public health in Brazil, appreciated by social security for the viability of the right and universal coverage to the services offered by this system. The high growth in costs due to the increase in technologies, changes in the demographic and epidemiological profile, judicialization and the austerity caused by Constitutional Amendment No. 29 and the coronavirus pandemic bring reflections on the ability to build new funding for the sustainability of SUS. The objective of this research was to identify the evidence in studies on the financing of this system for universal coverage of social security related to health in Brazil, through a narrative review of the literature, resulting in the analysis of 22 studies. Based on the results, we identified that the economic austerity measure and the costs of the pandemic impact the public deficit and undermine universal coverage and comprehensive health care for citizens. It is necessary to reconfigure the allocation of financial resources to guarantee the right to health services in the SUS. In addition, there is a need to change the culture and model of health management, implement quality issues and provide greater cooperation between federative entities in a solidary way with the strengthening of social participation.